2006
DOI: 10.1108/14684520610716162
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the moderating effect of industry on online behaviour

Abstract: Purpose -The main objective of the current work is to analyse the importance of the moderating effect of industry type on technological firms' behaviour and on the acceptance of online business management applications. Design/methodology/approach -The conceptual model, based on a technology acceptance model (TAM), has been tested across structural equation modelling techniques. Thus, a multi-sample analysis has been developed to study the significance of the effect on industry. Data were collected using e-mail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 64 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Thus the final interesting finding is that although Web 2.0 is often regarded as a radically new concept, the main critical success factors are similar to those in other projects involving IS development, such as the support of top management, proper leadership, communication and motivation and training of end‐users (Bandara et al , 2005; Hernández Ortega et al , 2006; Wong, 2005). Therefore a standard IS success model such as the Delone and McLean model can and should be applied.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Thus the final interesting finding is that although Web 2.0 is often regarded as a radically new concept, the main critical success factors are similar to those in other projects involving IS development, such as the support of top management, proper leadership, communication and motivation and training of end‐users (Bandara et al , 2005; Hernández Ortega et al , 2006; Wong, 2005). Therefore a standard IS success model such as the Delone and McLean model can and should be applied.…”
Section: Discussionmentioning
confidence: 98%
“…Their role would also be to encourage people with knowledge to contribute and to manage the structure of the articles.All companies should invest in the training of their employees irrespective of their position in the firm and their proficiency in computer or online information use. Training may also deliver a change in attitude about the ease of use and the achievement of routine use (Hernández Ortega et al , 2006). It is also an indication of management's support for a new initiative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that industry type moderates the relationships in strategy related models (e.g. Hitt, Ireland, & Stadter, 1982;Banerjee, Iyer & Kashyap, 2003;and Ortega, Martinez & Hoyos, 2006). Researcher in the field of strategy have also studied the firm age and firm size as moderating variables and proved that larger firms present more capability than smaller firms, and young firms can better exploit the resources than middle-aged-firms (e.g.…”
Section: Previous Studiesmentioning
confidence: 99%